The top 200 web sites for marketing - Walker, Mark (Kogan Page Limited, 2000)
This guide, accompanied by a CD-ROM, is intended for business users whose job function involves marketing or related activities, and who wish to find out what useful resources are available on the Internet. It is not a marketing textbook, but rather a tool primarily aimed at marketing professionals, students and business people keen to keep abreast of the developments and information sources in relation to marketing their products or services. The book lists the 200 top sites, grading each for its relevance and ease of use. The browser on the CD-ROM can be used to access material from the Internet and log on to an updating service.